PENGARUH MANAJEMEN KESISWAAN TERHADAP AKTIVITAS BELAJAR PAI SECARA DARING DI SEKOLAH ADHI MEKAR INDONESIA - Sudarsono, Sudarsono; Ayu Amelia (Nusantara Journal of Islamic Studies, 2023)
Student management in language is all matters relating to the arrangement of students in schools, aiming to increase the effectiveness and efficiency of school services so that knowledge, skills, and attitudes of students are developed through channeling aspirations and fulfilling needs. The scope of student management in the learning process is to regulate the presence and absence of students, grouping of students, guidance and monitoring. The formulation of the problem in this study examines aboutHow much student management contributes to PAI online learning activities at SD AMI Denpasar Bali. The purpose of this research is; (1) To find out the influence of student management on PAI online learning activities at SD AMI Denpasar Bali. (2) To find out how much contribution student management contributes to PAI online learning activities at SD AMI Denpasar Bali. This study uses quantitative research, with the respondents being Muslim students in SD AMI Denpasar. Data collection techniques used in this study using questionnaires and documentation. The results showed that: 1) there is a significant positive influence on student management on pai learning activities online at AMI Denpasar Elementary School, known thitung > ttabel, which is 2,662 > 1,717, so Ho was rejected and Ha accepted, meaning that the coefficient of meaningful correlation / significant 2) student management variable (X) has a simultaneous contribution of 19.6% to the variable of learning activity (Y) which is classified as low and the rest is 80.4% influenced by f Other actors who are not researched by the author.